Біологія Sus scrofa domesticus: відтворювальні якості свиноматок різної внутріпородної диференціації за індексом М. Д. Березовського та економічна оцінка їх використання - Халак, В. І.; Khalak, V. I.; Бордун, О. М.; Bordun, O. M.; Горчанок, Анна Володимирівна; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Gorchanok, A. V.; Чегорка, П. Т.; Chegorka, P. T.; Колбасіна, Т. В.; et al. (НААН, ДУ Інститут зернових культур, 2023)
Результати досліджень свідчать, що свиноматки підконтрольної популяції характеризуються високими показниками відтворювальних якостей. Так, багатоплідність свиноматок основного стада дорівнює 11,1 ± 0,14 поросят на один опорос, великоплідність – 1,41 ± 0,009 кг, молочність – 51,8 ± 0,82 кг, маса гнізда на час відлучення, у віці 30 діб – 74,3 ± 0,85 кг, збереженість – 94,6 %. Індекс вирівняності (однорідності) гнізда свиноматки за живою масою поросят на час їх народження дорівнює 5,21 ± 0,076 (Сv = 17,11 %), індекс М. Д. Березовського – 37,10 ± 0,378 бала (Сv = 11,90 %). Коефіцієнт варіації абсолютних показників відтворювальних якостей основних свиноматок коливається у межах від 7,88 (великоплідність, кг) до 18,52 % (молочність, кг). The paper presents the results of the study of the reproductive qualities of sows of different breeding value, evaluated according to the index of M. D. Berezovsky (I), and the economic efficiency of their use is calculated. It was established that the dominant number of sows of the large white breed of the controlled population (76.4 %) in terms of multifertility and nest weight at the time of weaning at the age of 60 days belong to the I class and the "elite" class. The maximum indicators of multifertility, (13.1 heads), milk yield (57.4 kg) and weight of the nest at the time of weaning at the age of 30 days (77.9 kg) are characterized by sows of the 1st experimental group (I = 40.00–50.58 points). In the animals of the II experimental group, the M.D. Berezovsky index ranges from 29.09 to 34.07 points. The use of sows of the I experimental group provides additional production at the level of +4.62 %, and its cost is equal to +173.77 UAH. / head / farrowing.
Biology of Sus scrofa domesticus: reproductive qualities of sows of different intrabreed differentiation according to the index M. D. Berezovsky and their economic evaluation using
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477
Keywords: вартість додаткової продукції; vartist dodatkovoi produktsii; свиноматка; svynomatka; відтворювальні якості; vidtvoriuvalni yakosti; племінна цінність; pleminna tsinnist